Validity and limitations of self-reported periodontal health - Buhlin K, Gustafsson A, Andersson K, Ha°kansson J, Klinge B. (Blackwell Synergy, 2002)
To study the agreement between self-reported dental conditions and clinical findings in an adult population (20–84 years of age), and thus evaluate questionnaires as a tool in epidemiological studies of oral health, in general, and periodontal health, in particular.